Efficacy of vector thermal pulsation treatment in reducing postcataract surgery dry eye disease in patients affected by meibomian gland dysfunction. Issue 4 (April 2023) - Mencucci, Rita; Mercuri, Stefano; Cennamo, Michela; Morelli, Alberto; Favuzza, Eleonora
Abstract : A single preoperative LipiFlow treatment was effective in preventing postcataract surgery DED in patients with mild-moderate MGD, with better results compared with warm compresses. Abstract : Purpose: To evaluate the effect of a single LipiFlow vector thermal pulsation treatment performed before cataract surgery in reducing signs and symptoms of postoperative dry eye disease (DED) in patients with mild-moderate meibomian gland dysfunction (MGD). Setting: Eye Clinic, Careggi Hospital, University of Florence, Florence, Italy. Design: Prospective unmasked randomized controlled clinical trial. Methods: This study included patients affected by age-related cataract and mild-moderate MGD, who were randomized into 2 groups: (1) a single LipiFlow treatment performed at 5 preoperative weeks and (2) warm compresses and eyelid massages twice a day for 1 preoperative month (control group). Noninvasive break-up time (NI-BUT), Schirmer test, Standard Patient Evaluation of Eye Dryness (SPEED) questionnaire, and MG functionality parameters were evaluated at visit 0 (5 preoperative weeks), visit 1 (1 preoperative week), and visit 2 (1 postoperative month). Confocal microscopy of the MG of lower eyelids was performed at visit 0 and visit 2. Results: A total of 46 patients (46 eyes) were enrolled. In the LipiFlow group (n = 23), NI-BUT, SPEED questionnaire, and MG functionality parameters significantly improved at visit 1 ( P < .05) and visit 2 ( P < .05) compared with baseline and remained stable postoperatively. In the control group (n = 23), they did not significantly improve after treatment, while worsened postoperatively. Moreover, the changes in all parameters from baseline were significantly different between the 2 groups. Confocal microscopy imaging highlighted lower postoperative MG alterations in the LipiFlow group. Conclusions: A single preoperative LipiFlow treatment was effective in preventing postcataract surgery DED in patients with mild-moderate MGD. Postoperatively, treated patients displayed a better ocular surface status compared with warm compresses.